PID Controller Implementation For Temperature Control In Leakage Current Test Chamber 20kv Insulator - Nugroho, Agung; Andromeda, Trias; Agus Riyadi, Munawar (International Journal of Advanced Engineering Research and Science, 2021)
The isolator is a device used in electric power systems which is very important to separate between conductor of the electric power systems transmission. Isolators are very influential on environmental conditions such as temperature, humidity and other pollutants. A suitable testing condition is needed to ensure the insulator will do properly. Therefore, it is necessary to test the insulator at a similar actual environment. This test is carried out using a chamber with temperature and humidity settings to determine the characteristics of the leakage current in the insulator.In this paper, a PID Controller is implemented to control the temperature in the chamber. The PID controller is applied in the Arduino R3 microcontroller using a DHT22 sensor and a thermoelectric cooling actuator (TEC12706.) Experimental results show that the PID controller can maintain the chamber temperature at the desired setpoint with Kp = 200, Ki = 10, Kd = 5. The system can reduce the temperature up to 23.6 °C with a rise time of 198 seconds with a peak time of 218 seconds at a temperature of 24.8 °C.The system can reach at apreset temperature value with a response time of 32 seconds.